Early season grazing effects on birch, grass, herbs and plant litter in coastal meadows used by reindeer: a short-term case study - Eilertsen, Svein M.; Schjelderup, Ivar; Mathiesen, Svein D. (Rangifer, 2002)
The effects of short-term grazing by reindeer (Rangifer tarandus tarandus) on birch (Betula pubescens), grasses, herbs and plant litter in coastal meadows in spring were investigated in grazed and control plots in 1996 and 1997. The meadow contained 29 different plant species, all but one of which (Deschampsia caespitosa) were intensively grazed by reindeer. Young birch eaten by reindeer did not increase in mean height (9 cm), while birch protected from grazing grew from 9 to 22 cm (P<0.05) during the two years of the experiment. The ratio of grasses to herbs was higher (P<0.05) in the grazed plots than in the control plots, and the relative abundace of grasses increased during the summer in both years. The abundance of Rumex asetosa and Alchemilla subcrenata decreased (P<0.05) in response to grazing. From spring 1996, plant litter increased (P<0.05) on the control plots until the investigation came to an end in spring 1998, unlike grazed vegetation. Reindeer affects the coastal meadows in northern Norway in spring by browsing on birch and grazing on herbs and grass which in the long term might influence the cultural landscape in favour of the growth of grass species.